Mr. S (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2023)
Prepare for plenty of giggles as a kindergarten class arrives for their first day of school but can't find their teacher—only a delicious-looking sandwich and the words "Mr. S" scribbled on the chalkboard. Chaos ensues as the kids argue whether the sandwich must be their teacher. A comical first-day-of-school book of mayhem and chaos by Monica Arnaldo, perfect for fans of Miss Nelson Is Missing. “This might be the funniest first-day-of-school book I’ve ever read." —Adam Rex, New York Times bestselling author of School’s First Day of School It was the first day of school. But even the kindergarteners of room 2B could tell something was seriously wrong. . . . Where was the teacher? Who left this sandwich on the desk? The only clue, written on the chalkboard, were three simple letters: Mr. S Praise for Mr. S: "Confusion, mystery, and laughs are on the menu in Arnaldo’s deliciously goofy back-to-school tale." —Publishers Weekly (starred review) "The tale's genuinely absurd situation, the mystery of the teacher's identity, and the deadpan storytelling make this a memorable read-aloud choice." —ALA Booklist (starred review) "Mysteries for young readers are few and far between and this one is fun and entertaining." —School Library Journal (starred review) An Amazon Best Book of the Month * A Junior Library Guild Selection * Indigo Staff Pick of the Month * Governor General's Literary Award Finalist * Publishers Weekly Best Book of the Year * Indigo Best Book of the Year * Chicago Public Library Best of the Best List * New York Public Library Best Book of the Year * School Library Journal Best Book of the Year * Booklist Editor's Choice